Grandmothers’ Familism Values, Adolescent Mothers’ Parenting Efficacy, and Children’s Well-Being - Zeiders, Katharine H. (J Fam Psychol, 2015)
The current study examined intergenerational processes related to familism values among grandmothers, adolescent mothers, and their children. Mexican-origin families (N = 180) participated in in-home interviews during adolescent mothers’ third trimester of pregnancy and 10-, 24-, 48-, and 60-months postpartum. Using longitudinal path analyses, we linked grandmothers’ familism values and behaviors to adolescent mothers’ parenting processes and, in turn, their child’s well-being, taking into account developmentally relevant needs of adolescent mothers. Results revealed that grandmothers’ familism values before the birth of the baby predicted child-rearing support and communication within the grandmother-adolescent mother dyad after the birth of the baby. Support, but not communication, was in turn predictive of adolescent mothers’ parenting self-efficacy, but only at high levels of autonomy granting within the grandmother-adolescent mother dyad. Finally, adolescent mothers’ parenting self-efficacy predicted children’s greater social competence (48 months old), which in turn, predicted greater academic functioning (60 months old). Our findings shed light on the behavioral correlates of familism values within Mexican-origin families with adolescent mothers and highlight the need to consider factors that are developmentally salient (e.g., autonomy) when understanding how familism behaviors benefit adolescent mothers and their children.